The Effect of Using Storytelling Method By Video Towards Students’ Speaking Skill at The Eighth Grade Students of MTs An-Nur Kemayoran Central Jakarta in Academic Year 2021/2022 - Mutmainnah, Fitri Nur; Gumelar, Rizdki Elang; Munawaroh, Tatu (Universitas Mathla'ul Anwar Banten, 2021)
The purpose of the study is to determine the effect of using storytelling method to improve students' speaking skill. Storytelling as the entire context of a moment when oral narration of stories in verse or in prose, is performed or led by one person before a live audience. The scope of this research focuses on analyzing the effect of using storytelling method by video toward students’ speaking skill. This research took quantitative approach, while the method used experimental with pre-test and post-test experimental class and control class design. The instrument used was achievement test. The subjects of this study were selected using random sampling. The results of the analysis of the pre- test and post-test experiments using the storytelling method showed an Sig (2-tailed) of 0.00 from the decision that if Sig (2-tailed) < 0.05 then the data was significant, meaning that the hypothesis was accepted. And if the result of Asymp Sig (2-Tailed) > 0.05 then the hypothesis is rejected. On the other word, there is any significant effect of Storytelling towards Students’ Speaking Skill.